Pengaruh Kaligrafi terhadap Perkembangan Seni Rupa di Dunia Islam - Ahmad Salabi As silmi (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2024)
Islamic calligraphy is a form of art that plays a central role in the development of Islamic culture and art. Highlighting the beauty of Arabic script, calligraphy serves not only as an aesthetic expression but also as a spiritual medium to reflect religious values. This article discusses how calligraphy influences the development of Islamic art through its integration with geometric designs, technical innovations, and applications across various media such as architecture, ceramics, textiles, metalwork, and glass. The dissemination of calligraphy to various regions, including Europe, Asia, and Africa, demonstrates its universal appeal. Moreover, the influence of calligraphy is evident in modern and contemporary art, ensuring its relevance in the era of globalization. With strong traditional roots and adaptability, Islamic calligraphy continues to symbolize harmony, beauty, and spirituality, inspiring the global art world